'Cash‐only' buprenorphine a threat to opioid crisis. Issue 9 (1st March 2019) - Knopf, Alison
Abstract : In an editorial written by the principal researcher on the clinical trials that led to the approval of buprenorphine‐naloxone to treat opioid use disorder, the increase in cash‐only buprenorphine clinics is called a threat to the opioid treatment system. "Proliferation of Cash‐Only Buprenorphine Treatment Clinics: A Threat to the Nation's Response to the Opioid Crisis, " by Art Van Zee, M.D., of the St. Charles Clinic, Stone Mountain Health Services, and David Fiellin, M.D., of the Yale University School of Medicine, was published in the March issue of the American Journal of Public Health .